Towards the accreditation of Southeast Asian zoos : the Malaysian experience. - Sunil Kumar Sharma, Reuben; Sugnaseelan, Sumita
Zoo accreditation and captive animal welfare have become issues of pivotal concern for zoological facilities worldwide. In South-east Asia, many establishments have become the focus of attention and their roles as centres of education and conservation have been questioned. As such, there is a driving need for standards to be established in areas of animal husbandry, enclosure design and animal welfare. With over 40 public and private zoological parks in Peninsular Malaysia, the establishment of guidelines on zoo management is of national concern.The Wildlife Conservation Act 2010 was gazetted to govern the conservation, utilisation, trade and welfare of wild animals. Following this, audits were conducted on various zoological facilities to evaluate their management practices and animal welfare standards. The proposed national zoo accreditation program emphasises on providing a suitable physical, physiological and psychological environment for the animals. Focal areas include space requirements,provision of suitable furniture, substrate and enrichment, feeding regime and diet, management of zoo records, improvement of waste management and sanitation, and protocols for safety, biosecurity and disease monitoring. It is envisaged that such a program, although laden with many challenges, will ensure the gradual improvement in the welfare standards of captive wild animals in the country.